Structural Abnormalities in Gambling Disorder Using Voxel-Based Morphometry - Bachar, Safiyyah (My University, 2021)
Gambling is a recreational activity popular across the globe, but maladaptive gambling behavior can pose serious, negative consequences to the gambler. Gambling disorder (GD) is a psychiatric disorder that focuses on these dysfunctional behaviors. In order to investigate the structural brain abnormalities in GD, a whole-brain exploratory analysis was carried out using voxel-based morphometry (VBM8). VBM8 was selected to enable direct comparison to an earlier study. There were no significant differences in global- or regional- gray and white matter volumes between GD patients and healthy controls (HC). These findings suggest that GD is not associated with macroscopic brain anatomical abnormalities or that anatomical abnormalities are too small compared to the individual variance to be detected with VBM8.
Keywords: gambling disorder, addiction, behavioral addiction, MRI, voxel-based morphometry